Sodium-ion battery negative electrode material and preparation method and application thereof

By using carbon cloth and porous structures of cobalt selenide and vanadium selenide nanosheets, the volume expansion and powderization problems during charging and discharging are solved, high magnification and cycle stability are achieved, and the The preparation process reduces costs.

CN119481037APending Publication Date: 2025-02-18SHANDONG HAIHUA GRP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411460660.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing sodium ion battery anode materials have volume expansion and powdering problems during charging and discharging, and lack sufficient large gap space to accommodate sodium, resulting in the formation of sodium dendrites.

Method used

The sodium ion battery negative electrode material consisting of carbon cloth and nanosheets interspersed with uniform dispersion of loads. The nanosheets are porous structures of cobalt selenide and vanadium selenide. It is prepared by hydrothermal treatment and high-temperature calcination, which simplifies the preparation process and reduces the cost. .

Benefits of technology

It effectively reduces the volume expansion problem during charging and discharging, greatly increases the active site for sodium storage, improves rate performance and cycle stability, and reduces the cost of materials and preparation complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481037A_ABST
    Figure CN119481037A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium-ion battery negative electrode material as well as a preparation method and application thereof, and belongs to the field of sodium-ion batteries. The negative electrode material comprises carbon cloth and nanosheets which are mutually interspersed and uniformly dispersed and loaded on the carbon cloth, the nanosheets are cobalt selenide and vanadium selenide, and the nanosheets are of a porous structure; the diameter of the negative electrode material is 10.4-18.6 [mu] m, the thickness of the nanosheet is 10-70 nm, and the aperture of the pores is 3-32 nm; the cobalt selenide accounts for 32.5-48.1% of the mass of the negative electrode material, and the vanadium selenide accounts for 21.4-30.7% of the mass of the negative electrode material. The problem of volume expansion generated in the charge-discharge process can be effectively relieved, active sites for sodium storage are greatly increased, the preparation method is simple in operation step, easy to implement, low in cost, high in charge-discharge rate and excellent in cycle stability, and due to the characteristics, the material has remarkable application potential in industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of sodium ion batteries, and in particular relates to a sodium ion battery negative electrode material and a preparation method and application thereof. Background Art

[0002] With the rapid development of clean energy, energy storage technology has become a key factor in promoting changes in the global energy structure. Among various energy storage technologies, electrochemical energy storage is considered to be the most widely used and has great potential. Among them, lithium-ion batteries, as a typical representative of electrochemical energy storage technology, have become one of the most viable options due to their high energy density, long cycle life, low self-discharge and environmental protection. However, limited lithium resources have become the main obstacle to the large-scale application of lithium-ion batteries. In contrast, sodium-ion batteries are similar to lithium-ion batteries in electrochemical reaction mechanism, and sodium resources are abundant, low cost and environmentally friendly. Therefore, sodium-ion batteries are regarded as a vital part of electrochemical energy storage systems. Therefore, it is imperative to find a suitable negative electrode material that has a large interstitial space and can easily store Na + , and can solve the problem of material volume expansion and pulverization during the circulation process.

[0003] The Chinese patent document with publication number CN111554896A discloses a cobalt selenide nickel nitrogen doped amorphous carbon nanocomposite negative electrode material and its preparation and application. The cobalt selenide nickel nitrogen doped amorphous carbon nanocomposite negative electrode material has a disordered porous structure, which increases the active sites of the material and is conducive to the transmission of sodium ions. However, the above preparation method requires the synthesis of a metal organic framework (MOF) first. The synthesis of MOF requires precise control of reaction conditions, including temperature, pressure and solvent selection, which increases the complexity and cost of the synthesis process.

[0004] The Chinese patent document with publication number CN109935791A discloses a carbon ball-wrapped cobalt selenide nanocomposite material, its preparation method and application. The nanocomposite material disperses cobalt selenide nanomaterials in porous carbon balls, which can accommodate the volume change of cobalt selenide nanomaterials during the charge and discharge process. However, the nanocomposite material lacks a large enough gap space to accommodate sodium, resulting in the formation of sodium dendrites. Summary of the invention

[0005] The purpose of the present invention is to provide a sodium ion battery negative electrode material and a preparation method and application thereof. The present invention can effectively reduce the volume expansion problem generated during the charge and discharge process, greatly increase the active sites for sodium storage, and the preparation method has simple operation steps, is easy to implement and has low cost, has a high charge and discharge rate, and excellent cycle stability. These characteristics make it have significant application potential in industrial production.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: The invention provides a sodium ion battery negative electrode material, comprising carbon cloth and nanosheets interlaced and uniformly dispersed and loaded on the carbon cloth, wherein the nanosheets are cobalt selenide and vanadium selenide, and the nanosheets are porous structures; the diameter of the negative electrode material is 10.4-18.6 μm, the thickness of the nanosheet is 10-70 nm, and the porous pore size is 3-32 nm; the cobalt selenide accounts for 32.5-48.1% of the mass of the negative electrode material, and the vanadium selenide accounts for 21.4-30.7% of the mass of the negative electrode material.

[0007] The present invention also provides a method for preparing a negative electrode material for a sodium ion battery as described in the above technical solution, comprising the following steps: (1) dispersing carbon cloth, cobalt source and urea in deionized water, performing hydrothermal treatment, and then washing with water and ethanol respectively until the supernatant is clear and drying to obtain treated carbon cloth; (2) The carbon cloth, selenium powder and vanadium source treated in step (1) are placed in three porcelain boats respectively, and the three porcelain boats are placed in a tubular furnace, with the selenium powder and vanadium source located on the upstream side of the airflow of the tubular furnace, and high-temperature calcination is performed in a hydrogen-argon mixed atmosphere to obtain a negative electrode material for a sodium ion battery.

[0008] Preferably, in step (1), the cobalt source is one of cobalt chloride, cobalt sulfate or cobalt nitrate; the concentration of the cobalt source is 0.01-0.5 mol / L; the molar ratio of the cobalt source to urea is 1:10-50; the hydrothermal treatment temperature is 100-180°C, and the time is 6-10 h; the drying temperature is 60-100°C, and the time is 6-8 h.

[0009] Preferably, in step (2), the vanadium source is one of vanadium chloride, vanadium sulfate or ammonium metavanadate, and the mass ratio of the treated carbon cloth, selenium powder and vanadium source is 1:2-5:2-6; the high-temperature calcination is controlled at a heating rate of 2-5°C / min, a temperature of 400-800°C, and a time of 1-5h.

[0010] The present invention also provides the use of the above-mentioned sodium ion battery negative electrode material as a sodium ion battery negative electrode.

[0011] The beneficial effects of the present invention are as follows: 1. The sodium ion battery negative electrode material provided by the present invention, selenide (CoSe and VSe2) has a large interlayer spacing, layered structure and excellent conductivity, which is conducive to the insertion and deintercalation of sodium ions and alleviates the volume expansion problem, so it shows better rate performance and cycle performance in sodium ion batteries. In particular, compared with single metal selenides, bimetallic selenides have richer sodium ion diffusion kinetics and therefore have higher sodium insertion capacity, which helps to improve the energy storage density and performance of sodium ion batteries.

[0012] 2. The CoSe and VSe2 nanosheets used in the present invention have the characteristics of large surface area, sufficient exposed edge sites, etc., which can alleviate the negative impact of the volume expansion of metal selenides during the charging and discharging process, improve the interaction between the negative electrode / electrolyte, and thus improve the cycle stability of the battery; at the same time, the nanosheets have ultra-thin thickness and porous morphology, which can quickly realize electron / ion transmission and promote electrolyte penetration, effectively realize electron transfer between active materials and increase active sites for sodium storage, thereby showing excellent rate capability and cycle capacity; in addition, the interpenetration between the nanosheets exposes more free volume to store sodium to adapt to large volume changes.

[0013] 3. The carbon cloth (CC) in the material of the present invention has super strength and can maintain stability under high temperature conditions; CC has a high surface area and can effectively improve the wettability of the electrolyte; CC is conductive, which helps to form an efficient conductive network for electron transport and provides a buffer space for the dispersion of CoSe and VSe2, which is beneficial to the full exposure of active sites.

[0014] 4. The preparation method of the negative electrode material of the sodium ion battery provided by the present invention includes two simple chemical synthesis steps and has many advantages: ① Economic benefit: the raw materials (carbon cloth, cobalt source, urea, selenium powder and vanadium source) used are of low cost, and the hydrothermal synthesis technology itself is also an economical synthesis method; ② Ease of operation: the steps of the synthesis process are clearly divided, the operation is simple and intuitive, and there is no need to rely on complex templates or external structures for assistance; ③ Mild synthesis conditions: the hydrothermal synthesis step is implemented at a lower temperature and pressure, which effectively reduces energy consumption and equipment requirements; ④ Good scalability: the hydrothermal synthesis and subsequent calcination steps are suitable for scale-up production of different scales, which is conducive to the transformation from laboratory to industrial production; ⑤ Component adjustability: by adjusting the proportion of raw materials, the chemical composition and physical properties of the final product can be easily controlled to meet different performance requirements; ⑥ Environmental friendliness: water and ethanol are used as solvents in the synthesis process, and the entire preparation process is environmentally friendly, reducing the impact on the environment; ⑦ Simplified post-processing: the synthesized material can be directly applied to battery assembly without complex post-processing, simplifying the production process.

[0015] 5. The sodium ion battery negative electrode material prepared by the method of the present invention performs outstandingly in the application of sodium ion battery negative electrode. The specific capacities at current densities of 0.1, 0.2, 0.5, 1, 2 and 5 A / g are 524.6-530.2, 490.3-503.6, 455.7-461.8, 404.1-424.0, 339.8-352.2 and 302.4-311.9 mAh / g, respectively. At the same time, at 0.2A / g@100 cycles, the capacity retention rate can be maintained at 86.1-88.3%. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 A scanning electron microscope (SEM) image of the sodium ion negative electrode material prepared in Example 1; Figure 2 This is a magnified SEM image of the sodium ion negative electrode material prepared in Example 1; Figure 3 The X-ray diffraction (XRD) pattern of the sodium ion negative electrode material prepared in Example 1; Figure 4 This is a rate performance diagram of the sodium ion negative electrode material prepared in Example 1; Figure 5 The cycle stability of the sodium ion negative electrode material prepared in Example 1 at 0.2 A / g. DETAILED DESCRIPTION

[0017] The present invention is described in detail below with reference to the embodiments and comparative examples, but the present invention is not limited thereto. Example 1

[0018] (1) Carbon cloth, cobalt nitrate and urea were dispersed in 50 ml of deionized water, and then transferred to an oven at 150°C for hydrothermal treatment for 10 h; the carbon cloth was rinsed with water and ethanol in turn and dried in an oven at 60°C for 8 h, and the treated carbon cloth was collected; wherein the concentration of cobalt nitrate was 0.2 mol / L; and the molar ratio of cobalt nitrate to urea was 1:10; (2) The carbon cloth, selenium powder and vanadium chloride treated in step (1) are placed in three porcelain boats respectively, and the three porcelain boats are placed in a tubular furnace, with the selenium powder and vanadium chloride located on the upstream side of the gas flow. The temperature is then raised to 800°C at a heating rate of 5°C / min in a hydrogen-argon mixed atmosphere and kept warm for 1 hour. After naturally cooling to room temperature, a sodium ion battery negative electrode material (CC@CoSe / VSe2) is obtained; wherein the mass ratio of the mixture, selenium powder and vanadium source is 1:5:6.

[0019] The sodium ion battery negative electrode material obtained in this embodiment has a diameter of 10.4-12.0 μm, a thickness of 10-70 nm, a porous pore size of 3-32 nm, cobalt selenide accounts for 41.7% of the negative electrode material mass, and vanadium selenide accounts for 25.6% of the negative electrode material mass. Example 2

[0020] (1) Carbon cloth, cobalt chloride and urea were dispersed in 50 ml of deionized water, and then transferred to an oven at 180°C for hydrothermal treatment for 6 h; the carbon cloth was rinsed with water and ethanol in turn and dried in an oven at 80°C for 6 h, and the treated carbon cloth was collected; wherein the concentration of cobalt nitrate was 0.01 mol / L; and the molar ratio of cobalt nitrate to urea was 1:25; (2) The carbon cloth, selenium powder and ammonium metavanadate treated in step (1) are placed in three porcelain boats respectively, and the three porcelain boats are placed in a tubular furnace, with the selenium powder and vanadium chloride located on the upstream side of the gas flow. The temperature is then raised to 400°C at a rate of 2°C / min in a hydrogen-argon mixed atmosphere and kept at this temperature for 5 h. After naturally cooling to room temperature, CC@CoSe / VSe2 is obtained. The mass ratio of the mixture, selenium powder and vanadium source is 1:2:2.

[0021] The sodium ion battery negative electrode material obtained in this embodiment has a diameter of 11.7-18.6 μm, a thickness of the nanosheets of 26-65 nm, a porous pore size of 10-25 nm, cobalt selenide accounting for 32.5% of the mass of the negative electrode material, and vanadium selenide accounting for 21.4% of the mass of the negative electrode material. Example 3

[0022] (1) Carbon cloth, cobalt sulfate and urea were dispersed in 50 ml of deionized water, and then transferred to an oven at 100 ° C for hydrothermal treatment for 8 h; rinsed with water and ethanol respectively and dried in an oven at 100 ° C for 8 h, and the treated carbon cloth was collected; wherein the concentration of cobalt sulfate was 0.5 mol / L; the molar ratio of cobalt nitrate and urea was 1:50; (2) The carbon cloth, selenium powder and vanadium sulfate treated in step (1) are placed in three porcelain boats respectively, and the three porcelain boats are placed in a tubular furnace, with the selenium powder and vanadium chloride located on the upstream side of the gas flow. The temperature is then raised to 600°C at a heating rate of 3°C / min in a hydrogen-argon mixed atmosphere and kept at this temperature for 3 h. After naturally cooling to room temperature, CC@CoSe / VSe2 is obtained; wherein the mass ratio of the mixture, selenium powder and vanadium source is 1:3:5.

[0023] The sodium ion battery negative electrode material obtained in this embodiment has a diameter of 12.0-16.1 μm, a thickness of the nanosheets of 15-55 nm, a porous pore size of 5-30 nm, cobalt selenide accounting for 48.1% of the mass of the negative electrode material, and vanadium selenide accounting for 30.7% of the mass of the negative electrode material. Comparative Example 1

[0024] In this comparative example, no selenium powder was added, and the other processes were the same as those in Example 1.

[0025] The sodium ion battery negative electrode material obtained in this comparative example has a diameter of 8.1 to 9.3 μm. Comparative Example 2

[0026] In this comparative example, no vanadium powder was added, and the other processes were the same as those in Example 1.

[0027] The sodium ion battery negative electrode material obtained in this comparative example has a diameter of 10.8-11.3 μm, a thickness of 15-30 nm, a porous pore size of 10-20 nm, and cobalt selenide accounts for 53.6% of the mass of the negative electrode material. Comparative Example 3

[0028] In this comparative example, no carbon cloth was added, and the other processes were the same as those in Example 1.

[0029] In the sodium ion battery negative electrode material obtained in this comparative example, the cobalt selenide accounts for 68.6% of the mass of the negative electrode material, and the vanadium selenide accounts for 31.4% of the mass of the negative electrode material.

[0030] Performance Testing: The negative electrode material obtained according to the embodiment and the comparative example was directly used as the negative electrode sheet, the metal sodium sheet was used as the counter electrode, 1 mol / L NaClO4 EC / DEC / FEC (1:1:2 Vol%) solution was used as the electrolyte, and whatman's adhesive-free glass fiber filter paper was used as the diaphragm. 2032 type button cells were assembled in an argon atmosphere glove box. The test results are shown in Table 1:

[0031] The CC@CoSe / VSe2 negative electrode material obtained in Example 1 was tested by scanning electron microscopy, and the obtained SEM image is as follows: Figure 1 and 2 As shown. The negative electrode material of the sodium ion battery includes carbon cloth and nanosheets interlaced and uniformly dispersed on the carbon cloth, the nanosheets are CoSe and VSe2, and the nanosheets are porous structures; the diameter of the negative electrode material is 10.4-12.0 μm, the thickness of the nanosheet is 10-70 nm, and the porous pore size is 3-32 nm. CoSe and VSe2 nanosheets benefit from their large interlayer spacing and excellent conductivity characteristics, and show better charge and discharge rates and cycle performance in sodium ion battery applications.

[0032] In addition, by Figure 1 and 2It can be seen that the nanosheets of CoSe and VSe2, thanks to their large surface area and sufficient edge active sites, help to alleviate the adverse effects of volume expansion of metal selenides during charge and discharge cycles, while improving the interaction between the negative electrode and the electrolyte, thereby enhancing the cycle stability of the battery. The ultra-thin characteristics and porous structure of the nanosheets are conducive to accelerating the transmission of electrons and ions, promoting the penetration of the electrolyte, effectively realizing the electron transfer between active materials, and increasing the active storage sites of sodium, showing excellent rate performance and cycle life. CC exhibits extremely high strength and can maintain its structural stability under high temperature environments; its abundant surface area helps to improve the wettability of the electrolyte; the conductive properties of CC help to build an efficient electron transport network and provide dispersed buffer space for CoSe and VSe2 nanosheets, which is conducive to the full exposure of active sites, thereby further improving battery performance.

[0033] The CC@CoSe / VSe2 negative electrode material prepared in Example 1 was subjected to XRD analysis, and the results are shown in Figure 3 . From the observation of the spectrum, it can be seen that the diffraction peaks of CoSe and VSe2 in the negative electrode material are both included and show clear crystalline characteristics, which indicates that the synthesized material has a high purity. In addition, there is a significant broad diffraction peak in the range of 17.6-25.8°, which indicates that CC is contained in the negative electrode material.

[0034] The prepared CC@CoSe / VSe2 negative electrode material was subjected to electrochemical tests, such as Figure 4 and 5 As shown. The specific capacities of the CC@CoSe / VSe2 negative electrode material prepared in Example 1 at current densities of 0.1, 0.2, 0.5, 1, 2 and 5 A / g were 530.2, 503.6, 461.8, 424.0, 352.2 and 311.9 mAh / g, respectively. Even after 100 cycles at 0.2 A / g, the capacity retention rate reached 88.3%, showing excellent charge and discharge performance and cycle stability. The same test was performed on the materials of Examples 2 and 3, and the results were similar to those of Example 1 (Table 1). The difference in capacity retention of the samples in each example at a current density of 0.2 A / g did not exceed 2.2%.

[0035] Compared with the samples of Comparative Examples 1 and 2, the examples have better performance under different rates and cycle conditions, indicating that selenide or bimetallic selenide has richer sodium ion diffusion kinetics, and therefore has a higher sodium insertion capacity, which helps to improve the energy storage density and performance of sodium ion batteries. (Table 1). In addition, as for Comparative Example 3, since the negative electrode material does not have CC, the wettability of the negative electrode material is poor, and it cannot provide a dispersed buffer space for CoSe and VSe2 nanosheets, which is not conducive to the full exposure of active sites, thereby significantly reducing the cycle reversibility and capacity retention.

[0036] The above-described specific embodiments further illustrate the present invention in detail, but these descriptions cannot be understood as limiting the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A sodium ion battery negative electrode material, characterized in that: The sodium ion negative electrode material comprises carbon cloth and nanosheets interlaced and uniformly dispersed and loaded on the carbon cloth, wherein the nanosheets are cobalt selenide and vanadium selenide, and the nanosheets are porous structures; the diameter of the negative electrode material is 10.4-18.6 μm, the thickness of the nanosheet is 10-70 nm, and the porous pore size is 3-32 nm; the cobalt selenide accounts for 32.5-48.1% of the mass of the negative electrode material, and the vanadium selenide accounts for 21.4-30.7% of the mass of the negative electrode material.

2. The method for preparing the negative electrode material for a sodium ion battery according to claim 1, comprising the following steps: (1) dispersing carbon cloth, cobalt source and urea in deionized water, performing hydrothermal treatment, and then washing with water and ethanol respectively until the supernatant is clear and drying to obtain treated carbon cloth; (2) The carbon cloth, selenium powder and vanadium source treated in step (1) are placed in three porcelain boats respectively, and the three porcelain boats are placed in a tubular furnace, with the selenium powder and vanadium source located on the upstream side of the airflow of the tubular furnace, and high-temperature calcination is performed in a hydrogen-argon mixed atmosphere to obtain a negative electrode material for a sodium ion battery.

3. The preparation method of the sodium ion battery negative electrode material according to claim 2, characterized in that, In the step (1), the cobalt source is one of cobalt chloride, cobalt sulfate or cobalt nitrate; the concentration of the cobalt source is 0.01-0.5 mol / L; the molar ratio of the cobalt source to urea is 1:10-50; the hydrothermal treatment temperature is 100-180°C, the time is 6-10h; the drying temperature is 60-100°C, and the time is 6-8h.

4. The method for preparing a negative electrode material for a sodium ion battery according to claim 2, characterized in that: In the step (2), the vanadium source is one of vanadium chloride, vanadium sulfate or ammonium metavanadate, and the mass ratio of the treated carbon cloth, selenium powder and vanadium source is 1:2-5:2-6; the high-temperature calcination is controlled at a heating rate of 2-5°C / min, a temperature of 400-800°C, and a time of 1-5h.

5. An application of the negative electrode material for sodium ion batteries as claimed in claim 1, characterized in that: The sodium ion battery negative electrode material is used for the negative electrode of the sodium ion battery.

Citation Information

Patent Citations

  • Carbon sphere coated cobalt selenide nano-composite material and preparation method and application thereof

    CN109935791A

  • Cobalt nickel selenide nitrogen-doped amorphous carbon nano composite negative electrode material as well as preparation and application thereof

    CN111554896A